Heritage of darkness : a Chloe Ellefson mystery - Ernst, Kathleen, 1959- (Ernst, Kathleen, 1959- Chloe Ellefson mystery., 2013)
"Dark Secrets Hidden in Norwegian Traditions. For curator Chloe Ellefson, a family bonding trip to Decorah, Iowa, for rosemaling classes seems like a great idea--until the drive begins. Chloe's cop friend Roelke takes her mother's talk of romantic customs good-naturedly, but it inflates Chloe's emotional distress higher with each passing mile. After finally reaching Vesterheim Norwegian-American Museum, Chloe's resolve to remain positive is squashed when she and Roelke find Petra Lekstrom's body in one of the antique immigrant trunks. Everyone is shaken by the instructor's murder, and when Mom volunteers to take over the beginners' class, Chloe is put in the hot seat of motherly criticism. As she investigates, Chloe uncovers dark family secrets that could be deadly for Mom . . . and even herself"--Provided by the publisher.